ChrisFroome. Body Composition & Aerobic Physiology Report - Bell, P.; Furber, M. (2015)
On Monday 17th August, the GSK Human Performance Lab welcomed two-Ame Tour de France Champion, Chris Froome, for a series of physiological and body composition assessments. These assessments provided rich data, which would aid and inform Chris`s preparation for Rio 2016 by providing a baseline from which progression and improvement can be measured. It also serves to quantify the integral components of Chris`s physiology that make him an exceptional endurance athlete. As requested by Froome himself, we are now providing full visibility of the report our scientists delivered to him. The report can be seen below.